Explicit Lexical Collocation Instruction in Online Teaching - Cao Yen Ngoc (IGI Global, 2024)
This present study aims to investigate the impact of explicit lexical collocation instruction on Vietnamese students' vocabulary use and their attitudes on the explicit lexical collocation instruction during online teaching due to COVID-19. Participants were 47 EFL students, divided into the experimental group and the control group learning online via Google Meet. Results collected from two writing tests (pre and posttest) and semi-structured interview demonstrated that the vocabulary use in students' writing performance in the experimental group had a significant improvement after receiving the explicit lexical collocation instruction online and students had positive attitude toward the explicit lexical collocation instruction. It is recommended that the application of explicit lexical collocation instruction at the beginning of a writing period in EFL teaching. It is recommended that EFL teachers can integrate lexical collocation instruction into teaching writing online to improve students' English proficiency in terms of quality of vocabulary use and writing performance.